Pengaruh Pelaksanaan Perda Tibum Terhadap Aksi Penyerobotan Fasum Untuk Sarana Berjualan oleh Pedagang Kaki Lima Di Kota Padang - Gokma Toni Parlindungan S (Journal of Global Legal Review, 2024)
The encroachment of public facilities (Fasum) as a place of business by street vendors  in Padang was once rampant. The existence of the Perda Ketertiban Umum dan ketentraman masyarakat (Perda Tibum) Number 11 Year 2005 has not been able to completely eradicate the encroachment. This study aims to analyze the influence of the implementation of the Peraturan Daerah (Perda) on the Arrangement and Development of Street Vendors (Perda Tibum) on the encroachment of Public Facilities (Fasum) by Street Vendors in Padang. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation studies. The results of the study show that the implementation of Perda Tibum has not been fully effective in preventing the encroachment of Fasum by Street Vendors. This is caused by several factors, such as the lack of socialization of Perda Tibum to Street Vendors, weak law enforcement, and limited public space available to accommodate Street Vendors. This study recommends several steps to increase the effectiveness of the implementation of Perda Tibum, such as strengthening the socialization of Perda Tibum to Street Vendors, increasing law enforcement, and providing adequate public space to accommodate Street Vendors.